Tashmim Al’ab Lughawiyah Li Ta’lim Al ’Anasir Al-Lughawiyah Min Khilali Al-Mufradat Al-Arabiyah Bayna Yadayk Al-Juz Al-Awwal - Afif Ramdhan Putra; Hadil Ismail Hasan (Ukazh: Journal of Arabic Studies, 2021)
تعد اللغة وسيلة التواصل والتفاهم الأساسية بين البشر وتعد اللغة العربية بجمالها وخصائصها ومنها عناصر لغوية التي هي أساس بنيت عليه اللغة نفسها، لذا ينبغي للمعلم والمتعلم للناطقين بغيرها لمعرفة اللغة العربية بوسيلة من وسائل التعليم ألا وهي ألعاب لغوية من خلال المفردات المقترحة من "كتاب العربية بين يديك الجزء الأول"، بحيث إنها تعين الطلابة على فهم اللغة وترقيتها وبيان كيفية الاستفادة منها في إثراء لغة الطلاب المبتدئين. Language is the main means of communication and understanding between humans and Arabic considered with their beauty and characteristics, including the linguistic elements which form the basis on which language is built, so that teachers and students for speakers of other languages must know Arabic through educational facilities, which is a linguistic game through the proposed vocabulary from "Arabic Book Bayna Yadayk, Part One," because it helps students gain understanding of language, promote it, and show how to use it to enrich the language of beginner students.